2004
DOI: 10.1002/elsc.200400009
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Hydrogen Production from Sucrose Using an Acid‐Enriched Sewage Sludge Microflora

Abstract: A novel and high-rate anaerobic sequencing bath reactor (ASBR) process was used to evaluate the hydrogen productivity of an acid-enriched sewage sludge microflora at a temperature of 35 C. In this ASBR process a 4 h cycle, including feed, reaction, settle, and decant steps, was repeatedly performed in a 5 L reactor. The sucrose substrate concentration was 20 g COD/L; the hydraulic retention time (HRT) was maintained at 12±120 h at the initial period and thereafter at 4±12 h. The reaction/settle period ratio, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The volumetric production rate and specific H 2 production rates from the sequencing batch reactor were comparable with CSTR values, while the upper value of VSS was higher (Table 3). Lin and Chou [34] using the same sequencing batch system report the high alkalinities occurring (> 6 g l −1 as CaCO 3 ), presumably due to operation at pH 6.7. This may give rise to problems of alkali consumption in the overall process.…”
Section: Reactor Typesmentioning
confidence: 94%
See 1 more Smart Citation
“…The volumetric production rate and specific H 2 production rates from the sequencing batch reactor were comparable with CSTR values, while the upper value of VSS was higher (Table 3). Lin and Chou [34] using the same sequencing batch system report the high alkalinities occurring (> 6 g l −1 as CaCO 3 ), presumably due to operation at pH 6.7. This may give rise to problems of alkali consumption in the overall process.…”
Section: Reactor Typesmentioning
confidence: 94%
“…Inocula are commonly pretreated to select for spore formers and destroy methanogens. Lin and Chou [34] investigated acid treatment (pH 3-4 with HCl for 24 h) of waste activated sludge from a municipal sewage treatment works. This inoculum has been used to develop the carrier-induced granular sludge bed reactor [35,36].…”
Section: Inocula and Start-up For Hydrogen Productionmentioning
confidence: 99%
“…Even though the latter approach is convenient in evaluating the overall process performance, it is challenging to use VS or COD as a gross substrate. In addition, not all portion of VS or COD is available to the substrate and microbes [27]. In this study, total carbohydrate (TC) in the reactor is used as the rate-limiting substrate.…”
Section: Kinetic Model Parametersmentioning
confidence: 99%
“…The value of B0 varies with temperature and type of substrate and manure. It was found that the value of B0 depends on the age of the manure, species, collection and storage, ration, and bedding material [23,27].…”
Section: The Volume Of Hydrogen Produced Under Standard Condition Permentioning
confidence: 99%
See 1 more Smart Citation